Soil Bacteria in Urban Community Gardens Have the Potential to Disseminate Antimicrobial Resistance Through Horizontal Gene Transfer - Mafiz, Abdullah Ibn; He, Yingshu; Zhang, Wei; Zhang, Yifan (Frontiers in Microbiology, 2021)
Fifteen soil and 45 vegetable samples from Detroit community gardens were analyzed for potential antimicrobial resistance contamination. Soil bacteria were isolated and tested by antimicrobial susceptibility profiling, horizontal gene transfer, and whole-genome sequencing. High-throughput 16S rRNA sequencing analysis was conducted on collected soil samples to determine the total bacterial composition. Of 226 bacterial isolates recovered, 54 were from soil and 172 from vegetables. A high minimal inhibitory concentration (MIC) was defined as the MIC greater than or equal to the resistance breakpoint of Escherichia coli for Gram-negative bacteria or Staphylococcus aureus for Gram-positive bacteria. The high MIC was observed in 63.4 and 69.8% of Gram-negative isolates from soil and vegetables, respectively, against amoxicillin/clavulanic acid, as well as 97.5 and 82.7% against ampicillin, 97.6 and 90.7% against ceftriaxone, 85.4 and 81.3% against cefoxitin, 65.8 and 70.5% against chloramphenicol, and 80.5 and 59.7% against ciprofloxacin. All Gram-positive bacteria showed a high MIC to gentamicin, kanamycin, and penicillin. Forty of 57 isolates carrying tetM (70.2%) successfully transferred tetracycline resistance to a susceptible recipient via conjugation. Whole-genome sequencing analysis identified a wide array of antimicrobial resistance genes (ARGs), including those encoding AdeIJK, Mex, and SmeDEF efflux pumps, suggesting a high potential of the isolates to become antimicrobial resistant, despite some inconsistency between the gene profile and the resistance phenotype. In conclusion, soil bacteria in urban community gardens can serve as a reservoir of antimicrobial resistance with the potential to transfer to clinically important pathogens, resulting in food safety and public health concerns.